Going Green: Determinants of Carbon Emission Disclosure in Manufacturing Companies in Indonesia - Hermawan, Atang; Aisyah, Isye Siti; Gunardi, Ardi; Putri, Wiratri Yustia (International Journal of Energy Economics and Policy, 2018)
This study aims to gather empirical evidence on the influence of regulators, institutional ownership, firm size, and profitability to carbon emission disclosure. Measurements regarding the area of carbon emissions disclosure are conducted using checklists that are adopted and developed based on the information request sheets provided by the Carbon Disclosure Project (CDP). The population of this study are all manufacturing companies listed on the Indonesia Stock Exchange at the period of 2014-2016. Samples of this study are being chosen by using purposive sampling method; which obtained 22 manufacturing companies, that published their annual financial reports and sustainability reports during the observation period and disclose their carbon emissions. The data used are secondary data from Indonesia Stock Exchange. The analysis technique used is multiple linear regression analysis. The research results proved that the regulator has an effect on carbon emission disclosure, company size influences carbon emission disclosure, and profitability affects carbon emission disclosure, while institutional ownership does not affect carbon emission disclosure. Keywords: carbon emissions disclosure, regulator, institutional ownership, company size, profitability, Indonesia. JEL Classifcations: G3, L6, M1, Q5